Production of bioactive metabolites by submerged fermentation of the medicinal mushroom Antrodia cinnamomea: recent advances and future development. (19th May 2019) - Zhang, Bo-Bo; Guan, Yu-Yan; Hu, Peng-Fei; Chen, Lei; Xu, Gan-Rong; Liu, Liming; Cheung, Peter C. K.
Abstract: Edible and medicinal mushrooms have usually been considered as a sustainable source of unique bioactive metabolites, which are valued as promising provisions for human health. Antrodia cinnamomea is a unique edible and medicinal fungus widespread in Taiwan, which has attracted much attention in recent years for its high value in both scientific research and commercial applications owing to its potent therapeutic effects, especially for its hepatic protection and anticancer activity. Due to the scarcity of the fruiting bodies, the cultivation of A. cinnamomea by submerged fermentation appears to be a promising substitute which possesses some unique advantages, such as short culture time period and its high feasibility for scale-up production. However, the amount of fungal bioactive metabolites derived from the cultured mycelia of A. cinnamomea grown by submerged fermentation is much less than those obtained from the wild fruiting bodies. Hence, there is an urgent need to bridge such a discrepancy on bioactive metabolites between the wild fruiting bodies and the cultured mycelia. The objective of this article is to review recent advances and the future development of the mycelial submerged fermentation of A. cinnamomea in terms of enhancement for the production of fungal bioactive components by the optimization of culture conditions and the regulation of fungal metabolism. This review provides valuable information for further biotechnological applications of A. cinnamomea as well as other mushrooms being the source of bioactive ingredients by submerged fermentation.